Penguatan Kepemimpinan Siswa Berbasis Nilai-Nilai Pendidikan Islam Melalui Kegiatan Latihan Dasar Kepemimpinan - Sholihan; Ansharuddin M; Nur Syarifuddin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
The development of students in the digital age presents challenges in shaping leadership rooted in moral and spiritual values. The tendency towards pragmatism and individualism has an impact on weak collective responsibility and low ethical awareness in student organisation practices. In the context of Islamic education, leadership is understood as a mandate that demands integrity, justice, and exemplary character. Therefore, this study aims to strengthen the understanding and internalisation of Islamic leadership values through Student Leadership Basic Training (LDKS) activities.  The method used is an educational-reflective approach with stages of conceptual material delivery, group discussions, case studies, leadership simulations, and individual reflection. The evaluation was conducted using pre-test and post-test questionnaires to measure students' level of understanding before and after the activity, as well as participatory observation to identify the dynamics of value internalisation. The results showed a significant increase in students' understanding of leadership based on Islamic educational values. The percentage of students in the ‘good’ understanding category increased from 33.3% before the activity to 83.3% after the activity. No students were found in the ‘poor’ category after the intervention. In addition, the participants' reflective narratives showed a paradigm shift from leadership as structural domination to leadership as a moral responsibility and trust.